Opening and closing doors: The role of language in international opportunity recognition and exploitation. Issue 6 (December 2015) - Hurmerinta, Leila; Nummela, Niina; Paavilainen-Mäntymäki, Eriikka
Highlights: Language skills of the decision-maker are related to international opportunity recognition and exploitation. Language skills may create a knowledge corridor, which either encourages or prevents the decision-maker from seeing a greater number of international opportunities. Matching linguistic knowledge helps managers to recognise international opportunities, especially if it is accompanied by language diversity and deeper culture-specific knowledge. The impact of the linguistic knowledge corridor has decreased due to the emergence of English as business language and digitalisation. Abstract: This study focuses on the impact of language skills on international opportunity recognition and exploitation. Data were collected from Finnish food industry companies employing a mixed-methods research strategy. It was found that the linguistic knowledge of the decision-maker is related to international opportunity recognition and exploitation, potentially creating a 'knowledge corridor' that either encourages or prevents international opportunities from being seen. A 'matching linguistic knowledge' construct was developed to investigate this knowledge corridor. The findings indicate that matching linguistic knowledge steers managers in their recognition of international opportunities, but the importance of the knowledge corridor has decreased with the emergence of Business English.